Role of cholinergic innervation in biliary remnants of patients with biliary atresia - Yang, Jixin; Chen, Xiaoqing; Wang, Wenjing; Su, Yanwei; Liu, Keqin; Abudusalamu, Adila; Li, Dandan; He, Ying; Wang, Pusu; Xiong, Xiaofeng; Feng, Jiexiong (Frontiers in Pediatrics, 2024)
Objective Biliary innervation is considered important in regulating the function of bile ducts, whereas the role of innervation in the hepatobiliary system of patients with biliary atresia (BA) remains unknown. This current study aims to investigate the role of innervation in biliary remnants and analyze the relationship between the innervation and prognosis of BA after surgery. Methods Eighty-seven patients with type III BA who underwent the Kasai procedure were consecutively enrolled from January 2017 to September 2020. Innervation and ductules in remnants were examined by pathologists. Liver function, onset of cholangitis, jaundice clearance, and survival with the native liver were recorded. Patients were followed up for 24 months. The relationship between innervation and prognosis was analyzed. Results In total, 67 patients had bile drainage postoperatively, and 21 biliary remnants contained neuronal plexuses where there was no neuron but nerve fiber bundles. Acetylcholinesterase staining was positive in all plexuses. In patients with bile drainage, those with plexuses had improved postoperative liver function, significantly better jaundice clearance 3 or 6 months postoperatively (50.0% vs. 19.1%, or 90.0% vs. 63.8%, respectively), fewer episodes of early cholangitis (10.0% vs. 34.0%), and better survival (80.0% vs. 61.7%) compared to those without. In addition, a larger area of plexuses was associated with a larger area of ductules (R2 = 0.786, p = 0.000), less frequent (p = 0.000) and later cholangitis onset (p = 0.012), and better jaundice clearance (p = 0.063). Conclusions Increased cholinergic innervation in biliary remnants may help reduce the onset of cholangitis and lead to better and earlier jaundice clearance. Thus, it improves the postoperative prognosis of patients with BA.